Speech by the Ambassador of Spain - Suñer y Ferrer, Tomás (1952)
With sincere gratitude I compare with you, in the name of Spain, this joyous celebration of our race. Peru, Hispanic illustrious stem trunk, by the voice of his glorious Universidad Mayor de San Marcos and the Society of Neuro-Psychiatry and Legal Medicine, exalts a symbol of our common culture to pay tribute to the genius of Ramón y Cajal.